Comparative effectiveness of activated dolomite phosphate rock and biochar for immobilizing cadmium and lead in soils. (March 2021) - Liu, Beibei; He, Zhenli; Liu, Ruliang; Montenegro, Andrea C.; Ellis, Martin; Li, Qinfen; Baligar, Virupax C.
Abstract: Sandy soils in Florida are vulnerable to toxic metal pollution, and it is necessary to identify desirable amendments for the remediation of metal contaminated soils. Sorption and incubation experiments were conducted to compare the effectiveness of dolomite phosphate rock (DPR), humic acid activated dolomite phosphate rock (ADPR) and biochar (BC) in immobilizing Cd 2+ and Pb 2+ in two representative agricultural soils in south Florida (Alfisol-Riviera and Spodosol -Ankona series). The results showed that the soils had a low sorption capacity for metals with maximum sorption of 0.767–3.30 mg/g. Application of amendments increased the maximum sorption by 4.2–4.8 times for Pb 2+ and 1.5–2.2 times for Cd 2+ in Alfisol soil, and 7.1–7.9 times for Pb 2+ and 1.7–3.1 times for Cd 2+ in Spodosol soil. ADPR was the most effective amendment for increasing the soil's sorption capacity for Cd 2+ and Pb 2+ . 0.01 M CaCl2 extractable metals in the contaminated soils were significantly decreased by all the amendments, especially ADPR, which reduced extractable Cd 2+ and Pb 2+ by 87.2 and 76.0% in Alfisol and 91.3 and 76.3% in Spodosol soil as compared to control. The amounts of extractable Cd 2+ and Pb 2+ were negatively correlated with soil pH and available P, indicating that the change of soil characteristics by amendments was the dominant mechanism for enhanced immobilization of metals in the contaminated soils. These results indicate that ADPR has great potential for remediating toxic levels of Cd 2+ and Pb 2+ in contaminated soils. Graphical abstract: Image 1 Highlights: Activated DPR (ADPR) and biochar were compared for immobilizing metals in two soils. The immobilizing effectiveness of amendments varied with metal and soil type. Activation with humic acid increased the immobilizing power of DPR for Cd 2+ and Pb 2+ . The immobilization of metals by ADPR is related to increased soil pH and available P.